Associations between mobility, cognition and callosal integrity in people with parkinsonism - Brett W. Fling; Marian L. Dale; Carolin Curtze; Katrijn Smulders; John G. Nutt; Fay B. Horak (NeuroImage: Clinical, 2016)
Falls in people with parkinsonism are likely related to both motor and cognitive impairments. In addition to idiopathic Parkinson's disease (PD), some older adults have lower body parkinsonism (a frontal gait disorder), characterized by impaired lower extremity balance and gait as well as cognition, but without tremor or rigidity. Neuroimaging during virtual gait suggests that interhemispheric, prefrontal cortex communication may be involved in locomotion, but contributions of neuroanatomy connecting these regions to objective measures of gait in people with parkinsonism remains unknown. Our objectives were to compare the integrity of fiber tracts connecting prefrontal and sensorimotor cortical regions via the corpus callosum in people with two types of parkinsonism and an age-matched control group and to relate integrity of these callosal fibers with clinical and objective measures of mobility and cognition. We recruited 10 patients with frontal gait disorders, 10 patients with idiopathic PD and 10 age-matched healthy control participants. Participants underwent cognitive and mobility testing as well as diffusion weighted magnetic resonance imaging to quantify white matter microstructural integrity of interhemispheric fiber tracts. People with frontal gait disorders displayed poorer cognitive performance and a slower, wider-based gait compared to subjects with PD and age-matched control subjects. Despite a widespread network of reduced white matter integrity in people with frontal gait disorders, gait and cognitive deficits were solely related to interhemispheric circuitry employing the genu of the corpus callosum. Current results highlight the importance of prefrontal interhemispheric communication for lower extremity control in neurological patients with cognitive dysfunction.